PERKEMBANGAN HALAL INDUSTRI SEBAGAI LANGKAH MEMBUMIKAN SISTEM EKONOMI SYARIAH - Nurifa Adha; Lukman Hakim; Yoga Bayu Nugroho; Nur Hidayana Hafid; Hikmatun Nikmah; Ani Faujiah (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
Indonesia with the largest Muslim community, may take a dominant role in the global halal industry. In order for industry halal can grow and develop rapidly so as to offset the Internasional economy, it is necessary to work hard to encourage the rise of Indonesian halal industry. We can use the halal industry with all its potential to encourage an increase in the value of foreign exchange reserves. Industrial halal are acceptable and desirable community itself and become a mainstay so as to move the real sector and the national economy it is necessary to foster a proper strategy for the development of halal industry in Indonesia. Keywords: Industry Halal, Economy, Syariah Economy System References Andhika, Aldi, Annisa, dan Ira. “Peluang Industri Halal Global di Tengah Pandemi Corona.” Komite Nasional Ekonomi Keuangan Syariah. Mei 2020. Arwani, Agus. “EKONOMI ISLAM SALAH SATU MODEL ALTERNATIF STRATEGI MEREKATKOKOHKAN NKRI” 2 No. 01 (Oktober 2015). Fathoni, MA, dan Tasya Hadi. “Potret Industri Halal Indonesia.” Jurnal Ilmiah Ekonomi Islam 6 no 3 (2020). “Kementerian Keuangan Republik Indonesia,” 2019. Lis, Siska. “Analisis Maqashid Syariah dalam Pengembangan Hukum Industri Halal di Indonesia.” Jurnal Law and Justice 3 No 2 (Oktober 2018): 96. Nandy. “Sistem Ekonomi Islam.” Gramedia Blog, t.t. https://www.gramedia.com/literasi/sistem-ekonomi-islam/. “State of Global Islamic Economy Report,” 2019. Sukoso, Wiryawan Adam, Kusnadi Joni, dan Sucipto. Ekosistem Industri Halal. Jakarta: Perpustakaan Nasional RI, 2020.